2022
DOI: 10.24191/jmeche.v19i3.19798
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Flow Analysis of Stainless Steel and Alumina Feedstock Used for 2C-PIM Process

Abstract: Within this research, rheological analysis and thermal properties of two component feedstock based on ceramic and metallic powders are carried out to understand their flow behaviour. Scanning electron microscopy (SEM), Differential Scanning Calorimeter (DSC), Thermogravimetric (TGA) and Capillary Rheometer were employed to set up optimum conditions for moulding, debinding and sintering process. DSC results defined the melting point for both backbone binder components were recorded at the same point, 55 oC. TGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this study, the shear sensitivity index (n) characteristics can also be evaluated. Previous studies have demonstrated that the optimal n value in the pseudoplastic flow phase is in the range of 0.5 to 0.7 [19]. The explanation is because the feedstock viscosity changes with the shear rate more quickly with a smaller n value, indicating how a high n value may lead to process instability and make it harder to control the sample quality.…”
Section: Rheological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the shear sensitivity index (n) characteristics can also be evaluated. Previous studies have demonstrated that the optimal n value in the pseudoplastic flow phase is in the range of 0.5 to 0.7 [19]. The explanation is because the feedstock viscosity changes with the shear rate more quickly with a smaller n value, indicating how a high n value may lead to process instability and make it harder to control the sample quality.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…The melt viscosity of recycled polymer blends was evaluated to learn more about the interaction of the polymers in the blend and how compatibilizers affect it. This study was conducted to find the feedstock's stability during the injection moulding process [19]. A feedstock's flow behaviour is preferably pseudoplastic, which means that as the shear rate increases, the viscosity drops.…”
Section: Rheological Propertiesmentioning
confidence: 99%